Hierarchical Organization of Lung Progenitor Cells: Is there An Adult Lung Tissue Stem Cell? - Stripp, Barry R. (American Thoracic Society, 2008)
Dynamic changes to the developing lung endoderm during the process of lung development result in the establishment of functionally distinct epithelial compartments that vary both in their cellular composition and mechanisms contributing to their maintenance in adulthood. This focused review compares the hierarchical organization of cells within slowly and rapidly renewing tissues as a basis to better understand cellular and molecular mechanisms regulating epithelial maintenance and repair in the lung.